THE INFLUENCE OF PERCEIVED ACCESSIBILITY, MERCHANT SALES PROMOTION, AND PAIN OF PAYING ON IMPULSE BUYING AMONG QRIS USERS AMONG GEN Z IN MANADO CITY - Melbourne Vichard Angelo Ratag; Imelda W J Ogi; Sjendry S R Loindong (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the effect of perceived accessibility, merchant sales promotion, and pain of paying on impulsive buying among Generation Z QRIS users in Manado City, both partially and simultaneously. This research is motivated by the rapid growth of QRIS usage in Indonesia, which reached a transaction value of IDR 317 trillion with more than 57 million active users in the second quarter of 2025, alongside the increasing phenomenon of unplanned purchasing behavior among Generation Z as the primary users of this digital payment technology. This study employs a quantitative approach with a causal design (explanatory research). The theoretical foundations used are the Stimulus-Organism-Response (S-O-R) Theory and Mental Accounting Theory. The study population consists of Generation Z QRIS users in Manado City, with a sample of 100 respondents determined using the Lemeshow formula and purposive sampling technique. Data were collected through a questionnaire measured using a Likert Scale. The analysis technique employed is multiple linear regression using IBM SPSS 27 software, encompassing validity tests, reliability tests, classical assumption tests, F-test, t-test, and coefficient of determination (R²) test. The results indicate that: (1) Perceived accessibility has a positive and significant effect on impulsive buying (t = 2.176; Sig. = 0.032); (2) Merchant sales promotion has a positive and significant effect on impulsive buying (t = 2.279; Sig. = 0.025); (3) Pain of paying has a positive and significant effect on impulsive buying and is the most dominant variable (t = 3.150; Sig. = 0.002; β = 0.314); (4) Simultaneously, all three variables have a positive and significant effect on impulsive buying (F = 9.972; Sig. < 0.001). The coefficient of determination (R²) of 0.238 indicates that the three independent variables explain 23.8% of the variation in impulsive buying, while the remaining 76.2% is influenced by other factors outside this research model.